Urban squares morphologies, contributes of a multidimensional analysis - Paio, A. (2018)
The word Square and the Latin – platea – derived terms (piazza, plaza, praça, piaţă) are used to identify a public space of an exceptional character that is morphologically distinct in the urban morphology. The study of urban morphology seeks to understand the spatial structure and character of the city by identifying the patterns of its elements and the process of its development. The characterizing traits of the urban square are diverse and their origin twofold: global properties, referred to its relationships within the whole grid, and local properties, depending on the intrinsic morphologic features of its space; what requires a multi-dimensional and multi-scale approach. This paper will present a multidimensional analysis of two Italian Tuscan historic squares and two Portuguese historic squares. The squares will be analysed from a simultaneous view of their attributes. Thus, it is proposed, in an ongoing joint research project, to address the limitations of traditional-descriptive urban morphology in dealing with this simultaneity. Developing the relations between formal attributes and intangible spatial properties, their identity and closeness may be disclosed by multivariate statistical analysis and computational techniques.